2020
DOI: 10.1177/0258042x20962994
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Workplace Spirituality and Psychological Capital on Employee Negativity

Abstract: This article examined the direct influence of workplace spirituality on employee negativity—organizational cynicism, counterproductive work behaviour and turnover intentions. The proposed framework also examined how psychological capital buffers the relationship between workplace spirituality and employee negativity. The sample of the study included 138 employees, working in different private and public sector organizations in Nepal. Linear regression analyses were employed to test the hypothesized direct rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 83 publications
2
10
0
1
Order By: Relevance
“…Similarly, Kalhori et al (2018) found that students’ spiritual well-being affected their PsyCap. On the other hand, Shrestha and Jena (2020) found no evidence that workplace spirituality could influence counterproductive work behaviour. Similarly, Beehner and Blackwell (2016) also found that workplace spirituality does not influence turnover intention.…”
Section: Literature Reviewmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, Kalhori et al (2018) found that students’ spiritual well-being affected their PsyCap. On the other hand, Shrestha and Jena (2020) found no evidence that workplace spirituality could influence counterproductive work behaviour. Similarly, Beehner and Blackwell (2016) also found that workplace spirituality does not influence turnover intention.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Many researchers have found empirical evidence showing that increased PsyCap leads to positive outcomes in the workplace such as job satisfaction (Kanengoni et al , 2018), organisational commitment (Gurbuz and Yildirim, 2019; Kanengoni et al , 2018), company loyalty (Avey et al , 2011), improved performance (Luthans et al , 2007) and improved well-being (Kanengoni et al , 2018). PsyCap is also known to have a negative relationship with undesirable behaviours in the workplace such as counterproductive work behaviour (Shrestha and Jena, 2020), higher rates of turnover intention (Avey et al , 2011), anxiety (Bakker and Demerouti, 2006) and organisational cynicism (Shrestha and Jena, 2020). Similarly, Chen and Lim (2012) found that individuals with high PsyCap had low absenteeism and exhibited minimal job-seeking behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirituality at work also helps create meaning and purpose in the work, promoting motivation and engagement (Fouché et al 2017;Van Wingerden and Van der Stoep 2018), in this way potentially mitigating the relationship between burnout and turnover intention. Moreover, spirituality at work may diminish organizational cynicism (Shrestha and Jena 2021) and thus enhance trust in co-workers and perceived organizational support, both of which may function as job resources attenuating the effect of burnout on turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is good evidence showing a positive relationship between organisation's commitment to improving quality of life and the reduction of stress levels and other mental health disorders (Shrestha & Jena, 2020). Related to occupational outcomes, the improvement of subjective well‐being (SWB), including evaluative, hedonic and eudemonic well‐being, and the mental component of quality of life (QOL) of working population were observed (Sakuraya et al., 2020).…”
Section: Introductionmentioning
confidence: 99%